Effectuation Spectra in Chinese High-Tech Entrepreneurship: Domain-Specific Logic Orientations and Cross-Border M&A - Yipeng Liu; Andrew Isaak (Mergers and acquisitions, entrepreneurship and innovation, 2016)
As the developing nations grow and experience rapid institutional transformation, research has begun to investigate the roles of culture, cognition and institutional context on entrepreneurship and innovation. This chapter aims to advance the entrepreneurial cognition literature by juxtaposing entrepreneurial effectuation, domain-specific expertise and ambiguity. By conducting a qualitative study of Chinese high-tech domestic and returnee entrepreneurs, the authors propose a spectrum between causation and effectuation and argue that the entrepreneur's perceived level of ambiguity may better explain differing logic orientations among entrepreneurs, contributing to our understanding of entrepreneurial cognition. The authors theorize that 1) individual actors and the level of institutional development jointly comprise the entrepreneur's logic orientation; 2) the level of perceived ambiguity mediates the strategy adopted by high-tech entrepreneurs; 3) the entrepreneur's logic orientation can be regarded as a continual spectrum from effectuation to causation. Finally, the logic orientation concept is applied to the context of cross-border Mergers and Acquisitions (M&A) from a process perspective and the implications and fit of logic orientation with the stages of cross-border M&A are discussed.
https://doi.org/10.1108/S1479-067X201615
Keywords: L26; D91; G34; D81; M13; O19; Z13; O32; 330; Effectuation; Entrepreneurial Cognition; Mergers and Acquisitions; Decision-Making; China; High-tech entrepreneurship